2016
DOI: 10.1155/2016/1568061
|View full text |Cite
|
Sign up to set email alerts
|

Sickled Erythrocytes Reversal and Membrane Stabilizing Compounds inTelfairia occidentalis

Abstract: Background and Purpose. Traditional management of sickle cell disease (SCD) is ubiquitous in Africa. In south-eastern Nigeria, Telfairia occidentalis (T. occidentalis) is strongly recommended for consumption by SCD patients, owing to its presumed therapeutic effect. This study investigates the antisickling and membrane regenerative potentials of T. occidentalis in sickled erythrocytes. Experimental Approach. Sickled erythrocytes obtained from SCD patients were treated with sodium metabisulphite (2%) to induce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 12 publications
(10 reference statements)
3
9
0
Order By: Relevance
“…Nwaoguikpe, 31 reported 75.27% and 69.63% hemoglobin polymerization inhibition of the crude aqueous and water-soluble extracts of T. occidentalis respectively using the spectrophotometric method. The reversal effects of the methanol and aqueous extracts of the leaves of TO was reported by Atabo et al 16 . The extractives used were different and the activities lower than that of the ethanol extract reported in this study.…”
Section: Resultssupporting
confidence: 48%
See 3 more Smart Citations
“…Nwaoguikpe, 31 reported 75.27% and 69.63% hemoglobin polymerization inhibition of the crude aqueous and water-soluble extracts of T. occidentalis respectively using the spectrophotometric method. The reversal effects of the methanol and aqueous extracts of the leaves of TO was reported by Atabo et al 16 . The extractives used were different and the activities lower than that of the ethanol extract reported in this study.…”
Section: Resultssupporting
confidence: 48%
“…The reversal effects of the methanol and aqueous extracts of the leaves of TO was reported by Atabo et al. 16 The extractives used were different and the activities lower than that of the ethanol extract reported in this study. The results from this study using the reversal and inhibitory antisickling model however gave much higher antisickling activities at lower concentration and indicated that the ethanol extract of TO can be used as prophylactic drug in offsetting sickling crisis as well as be administered during crisis to reduce vaso occlusion and hence pain.…”
Section: Resultssupporting
confidence: 42%
See 2 more Smart Citations
“…Earlier study had posited that hydrophobicity of shortchain aliphatic esters facilitated their integration into the membrane system, eliciting structural rearrangement that promoted membrane stability [77,78]. In agreement with the present results, previous findings had reported that short-chain aliphatic acids (octadecanoic acid and 16-octadecenoic acid), short-chain aliphatic esters (pentadecanoic acid, 14-methyl ester, and 9-octadecadienoic acid (Z)-, 2, 3-dihydroxypropyl ester), aldehyde (α-campholene aldehyde), nitro compound (cyclohexanespiro-5′,4′-methyl-2′-phenyl-2′-oxazoline), alcohol (borneol), and aliphatic compound (α-phellandrene) in silica gel fractionated aqueous and methanol extracts of Telfairia occidentalis stabilized sickle erythrocyte membrane against osmotic stress and deterred sickling [79].…”
Section: Discussionmentioning
confidence: 99%